2017
DOI: 10.1108/sbr-11-2016-0068
|View full text |Cite
|
Sign up to set email alerts
|

Value similarity and overall performance: trust in responsible investment

Abstract: International audiencePurpose: The research shows how overall performance can help foster trust in financial institutions. While a climate of is trust amongst investors and the general public towards financial institutions is since recent turmoils on the financial markets, we believe that mutual funds adopting overall performance can help recover a climate of trust due to the implied balance between economic, social and environmental performance. More specifically, overall performance promotes values that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In the banking context, customers from different cultures and countries will always compare their present banking experience with their banking experience of the past; they will also rely on the experiences other members of their ethnic group have with a particular bank (Herjanto and Gaur, 2011). For this reason, similarity involves an assessment of the buyer's belief that a salesperson will share collective interests and values (Bonnefon et al , 2017); therefore, similarity with customers is an extremely effective relationship-building strategy (Palmatier et al , 2006; Kunz and Seshadri, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the banking context, customers from different cultures and countries will always compare their present banking experience with their banking experience of the past; they will also rely on the experiences other members of their ethnic group have with a particular bank (Herjanto and Gaur, 2011). For this reason, similarity involves an assessment of the buyer's belief that a salesperson will share collective interests and values (Bonnefon et al , 2017); therefore, similarity with customers is an extremely effective relationship-building strategy (Palmatier et al , 2006; Kunz and Seshadri, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The peer effects can only work if the other client recommendation is authentic; therefore, advisors must have a good understanding of the clients and their peers. In this regard, value similarity; that is, the overlapping of the value set of the investments of the peer and the value set of the investor is likely to predict the success of the nudge (Bonnefon et al, 2017).…”
Section: Nudging For Responsible Financementioning
confidence: 99%
“…(Biong and Silkoset, 2017) showed that the employers placed the greatest weight to suppliers providing funds adhering to socially responsible investment (SRI) practices, followed by the suppliers' corporate brand credibility, the funds' expected return, and the suppliers' management fees. Second, employers with investment expertise emphasized expected returns and downplayed SR in their choice, whereas employers with stated CSRstrategies downplayed expected return and emphasized SR. (Bonnefon, et. al, 2017) found that funds with similar values are perceived as more trustworthy by investors.…”
Section: Ethical Banking and Major Areas Of Granting Loans And Invest...mentioning
confidence: 99%